Thermal, Structural, and Optical Analysis of a Balloon-Based Imaging System. (19th January 2017) - Borden, Michael; Lewis, Derek; Ochoa, Hared; Jones-Wilson, Laura; Susca, Sara; Porter, Michael; Massey, Richard; Clark, Paul; Netterfield, Barth
Abstract: The Subarcsecond Telescope And BaLloon Experiment, STABLE, is the fine stage of a guidance system for a high-altitude ballooning platform designed to demonstrate subarcsecond pointing stability over one minute using relatively dim guide stars in the visible spectrum. The STABLE system uses an attitude rate sensor and the motion of the guide star on a detector to control a Fast Steering Mirror to stabilize the image. The characteristics of the thermal-optical-mechanical elements in the system directly affect the quality of the point-spread function of the guide star on the detector, so a series of thermal, structural, and optical models were built to simulate system performance and ultimately inform the final pointing stability predictions. This paper describes the modeling techniques employed in each of these subsystems. The results from those models are discussed in detail, highlighting the development of the worst-case cold and hot cases, the optical metrics generated from the finite element model, and the expected STABLE residual wavefront error and decenter. Finally, the paper concludes with the predicted sensitivities in the STABLE system, which show that thermal deadbanding, structural pre-loading, and self-deflection under different loading conditions, and the speed of individual optical elements were particularly important to the resulting STABLE optical performance.